Thermal Image Scanning for the Early Detection of Fever Induced by Highly Pathogenic Avian Influenza Virus Infection in Chickens and Ducks and Its Application in Farms - Noh, Jin-Yong; Kim, Kyu-Jik; Lee, Sun-Hak; Kim, Jun-Beom; Kim, Deok-Hwan; Youk, Sungsu; Song, Chang-Seon; Nahm, Sang-Soep (Frontiers in Veterinary Science, 2021)
Highly pathogenic avian influenza (HPAI) is considered as one of the most devastating poultry diseases. It is imperative to immediately report any known outbreaks to the World Organization for Animal Health. Early detection of infected birds is of paramount importance to control virus spread, thus minimizing the associated economic loss. In this study, thermal imaging camera devices were used to detect change in the highest body temperature (HBT) of chickens and ducks as an early indicator of HPAI infection. The HBT of both chickens and ducks increased at least 24 h before the manifestation of clinical signs of HPAI infection, depending on the severity of the infection. The basal HBT was recorded for broiler chickens housed under small pen and normal farm conditions without intentional infection. A threshold cutoff of maximum HBT was established based on the circadian rhythm of normal HBT. This study suggests that thermal imaging of chickens and ducks is a promising tool to screen any potential HPAI-infected flock in order to expedite HPAI diagnosis.